Role of microRNA-7 and selenoprotein P in hepatocellular carcinoma - Marwa Tarek; Manal Louis Louka; Eman Khairy; Randa Ali-Labib; Doaa Zakaria Zaky; Iman F Montasser (Tumor Biology, 2017)
There is an obvious need to diagnose hepatocellular carcinoma using novel non-invasive and sensitive biomarkers. In this regard, the aim of this study was to evaluate and correlate both relative quantification of microRNA-7 using quantitative real time polymerase chain reaction and quantitative analysis of selenoprotein P using enzyme-linked immunosorbent assay in sera of hepatocellular carcinoma patients, chronic liver disease patients, as well as normal healthy subjects in order to establish a new diagnostic biomarker with a valid non-invasive technique. In addition, this study aimed to investigate whether changes in selenium supply affect microRNA-7 expression and selenoprotein P levels in human hepatocarcinoma cell line (HepG2). The results showed a highly significant decrease in serum microRNA-7 relative quantification values and selenoprotein P levels in malignant group in comparison with benign and control groups. The best cutoff for serum microRNA-7 and selenoprotein P to discriminate hepatocellular carcinoma group from benign and control groups was 0.06 and 4.30 mg/L, respectively. Furthermore, this study showed that changes in selenium supply to HepG2 cell line can alter the microRNA-7 profile and are paralleled by changes in the concentration of its target protein (selenoprotein P). Hence, serum microRNA-7 and selenoprotein P appear to be potential non-invasive diagnostic markers for hepatocellular carcinoma. Moreover, the results suggest that selenium could be used as an anticancer therapy for hepatocellular carcinoma by affecting both microRNA-7 and selenoprotein P.